Optimizing the Role of Land Digitalization in Preventing Land Certificate Forgery in a Structural Manner - Yono; Barthos, Megawati (Greenation Publisher & Yayasan Global Resarch National, 2025)
The increase in land certificate fraud cases highlights the shortcomings of Indonesia's traditional land management system. Because of this circumstance, the government has decided to digitize land through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) in an attempt to establish a system that is secure, effective, and transparent. The purpose of this study is to examine how land digitization functions in preventing land certificate forgery and assess its effectiveness and implementation challenges from a legal and technical perspective. Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA), Government Regulation Number 18 of 2021, and Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 1 of 2021 concerning Electronic Certificates are just a few of the laws and regulations that are examined using a normative juridical approach. According to the study's findings, the use of electronic certificates, or